A note on the increase of the operational function exp(λΣ_{k=1}^{n}A_{k}s^{p_k}) - Piętka, Marek (Annales Mathematicae Silesianae, 1990)
The main result of the paper is the estimation of the operational function of the exponential type which is the parametric one in the sense of the Mikusinski’s theory. The estimation may be applied in studying the behaviour of solutions of partial differential equations.